2013
DOI: 10.1371/journal.pone.0080663
|View full text |Cite
|
Sign up to set email alerts
|

Utility and Necessity of Repeat Testing of Critical Values in the Clinical Chemistry Laboratory

Abstract: ContextRoutine repeat testing of critical values is a long-standing practice in many clinical laboratories; however, its usefulness and necessity remain to be empirically established and no regulatory requirements yet exist for verification of the critical value results obtained by repeat analysis.ObjectiveTo determine whether repeat testing of critical values is useful and necessary in a clinical chemistry laboratory.MethodsA total of 601 chemistry critical values (potassium, n = 255; sodium, n = 132; calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…Regarding the technical advances in automation and quality management issue in the clinical laboratories over the past decades, routine repeat testing of each critical value have been questioned (10,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the technical advances in automation and quality management issue in the clinical laboratories over the past decades, routine repeat testing of each critical value have been questioned (10,16).…”
Section: Discussionmentioning
confidence: 99%
“…Given the attention to patient safety measures and importance of timely reporting of critical results, Vol.15 No.3 Summer 2020 IRANIAN JOURNAL OF PATHOLOGY several issues arose concerning the eligibility of repeating critical values (12). Several studies have been published regarding the utility of repeat critical testing (2,3,8,10,12).…”
Section: Introductionmentioning
confidence: 99%
“…19,20 When a measured value triggers its critical value boundaries, the report will change color and a pop-up window will show up in the laboratory information system (LIS) to remind the technician of the generation of critical value. The critical value will be verified before reporting to clinicians, including rechecking the specimen, repeating test, 23 or contacting with clinicians for confirmation. TA B L E 2 (Continued) ratio, and clinician response ratio, are applied for monitoring the whole process of laboratory critical value management.…”
Section: Design Of Laboratory Critical Value Notification System Anmentioning
confidence: 99%
“…However, a survey of CAP Q‐probe showed that routine repeat analysis of automated chemistry and hematology critical values is unlikely to be clinically useful and may adversely affect patient care . Niu et al . concluded that when the initial chemistry critical values are within the analytical measurement range, repeated testing does not improve accuracy and is therefore unnecessary and recommend performing repeat clinical testing on a case‐by‐case basis, rather than routinely.…”
Section: Discussionmentioning
confidence: 99%